2013
DOI: 10.1007/s11832-013-0535-2
|View full text |Cite
|
Sign up to set email alerts
|

Induced membrane technique for the treatment of congenital pseudarthrosis of the tibia: Preliminary results of five cases

Abstract: Purpose The purpose of this study was to evaluate the two-stage surgical technique combining induced membrane, spongy autograft and intramedullary fixation for the treatment of congenital pseudarthrosis of the tibia (CPT). Methods Three boys and two girls were treated by this technique between 2003 and 2008. All patients had type IV CPT in Crawford's classification. Four of them had a limited dystrophic form, whereas one case presented an extensive tibia bone dystrophy. The average age of patients at the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 29 publications
1
19
0
7
Order By: Relevance
“…Hence, most of the reported cases are segmental bone defect of the diaphyseal part of the long bones [5,11,[13][14][15][16][17][18][19][20][21][22]. In our experience, we used this technique mostly for the tibia and the femur but also for the humerus and the radius.…”
Section: Remaining Questionsmentioning
confidence: 99%
“…Hence, most of the reported cases are segmental bone defect of the diaphyseal part of the long bones [5,11,[13][14][15][16][17][18][19][20][21][22]. In our experience, we used this technique mostly for the tibia and the femur but also for the humerus and the radius.…”
Section: Remaining Questionsmentioning
confidence: 99%
“…Bone union with complete integration of the graft and cortical reconstitution is achieved between 1 year and 2 years postoperatively, depending on the underlying disease. Initially developed in septic pseudarthrosis excision in adults, this reconstructive procedure has also been applied to traumatic bone loss, tumour resection and reconstruction (Biau et al ., ; Villemagne et al ., ; Chotel et al ., ), congenital pseudarthrosis of the tibia (Gouron et al ., ; Pannier et al ., ) and reconstruction of bone defects in children (Gouron et al ., , ).…”
Section: Introductionmentioning
confidence: 97%
“…Gouron et al (8) and Pannier et al (9) reported its use in the treatment of congenital pseudarthrosis of the tibia, which resulted in satisfactory bony union. Villemagne et al (10) adopted this method to reconstruct the long bone defect following resection of the malignant bone tumor, indicating that this simple and reliable technique may lead to promising clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first study, the Masquelet technique has been widely used to resolve massive bone defects caused by different diseases and achieved clinical efficacy (8)(9)(10)(11)(12). However, efficacy in the cases managed by the Masquelet technique does not mean that this approach is optimal.…”
Section: Introductionmentioning
confidence: 99%